Is maternal smoking harmful to the physical growth of offspring at early childhood? - Kaczmarek, Maria; Młyńska, Dorota (Polskie Towarzystwo Antropologiczne, 1999)
The effect of maternal smoking on birth weight of their babies, the effects of smoking during lactation and in the post-weaning period on growth in height and weight of children up to the age of 7 years were investigated. The sample consisted of 1511 children (778 boys and 733 girls) examined at two follow-up studies in May and December 1997. Retrospective data on birth-weight, height and weight up to the present investigation were available from the child's health record book. The results of the investigation revealed more frequent occurrence of lower birth-weight among children born to mothers smoking during pregnancy than among those born to non-smokers. Similar results were also gained for children in the pre-school period.